P557 Robotic surgery significantly improves outcomes for patients with inflammatory bowel disease. (21st January 2022) - Karategos, A; Yassin, N
Abstract: Background: Patients with Inflammatory Bowel Disease (IBD) have a high likelihood of both surgical treatment at a young age and repetitive operative interventions. Therefore, development of novel surgical techniques to minimize operative trauma are crucial for this group of patients. Robotic Surgery represents the newest minimally invasive technology available to reduce the impact of surgery, but has mostly been used for colorectal cancer rather than for benign conditions. The purpose of this study was to assess the feasibility and clinical outcomes of robotic surgery for patients with IBD. Methods: This is a single-institution prospective study evaluating all IBD patients undergoing robotic surgery between October 2020 to November 2021 at our trust. Demographic data, perioperative and 30-day postoperative outcomes were assessed. The feasibility of the techniques and clinical outcomes were documented and data were analysed. Results: A total of ninety robotic cases were performed from October 2020 to November 2021. Of these, 20 were IBD (75% Crohn's disease). The M:F ratio was 1:1; median age was 41 (18–79) years, BMI of 25 (16–37) kg/m2. Eighty-four per cent of patients were treated with a biologic agent in the preceding 60 days. The 2 most commonly performed procedures were Right Hemicolectomy with intracorporeal anastomosis (44%) and subtotal colectomy with end ileostomy (22%). There were no conversions to open surgery. Return of gut function, as defined by tolerating oral diet and passing flatus, was noted within 48 hours in 85% of the patients (n=17). There was minimal blood loss and all patients were discharged on their baseline Hb with no need for iron replacement therapy or blood transfusion. The median length of hospital stay was 4.5 days (3–10). There was no reported mortality. The 30-day readmission rate was 5% (n=1). Conclusion: Robotic surgery for patients with IBD is feasible, safe and improves clinical and surgical outcomes. This novel approach ensures that surgery remains minimally invasive, leading to a significant reduction in length of hospital stay, a rapid postoperative recovery and an earlier return of gut function.